A Coaching Clinic Instructional Model for Vocational Photography Education: A One-Group Pretest–Posttest Study - Fahmi, Khairul; Sulistiyo, Urip; Sofyan, Sofyan (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
Vocational photography education requires instructional approaches that connect conceptual understanding, practical experience, digital workflow, and professional practices. However, photography learning in vocational schools may be constrained by limited specialist teachers, heterogeneous photographic devices, restricted practical facilities, and insufficient opportunities for structured practice. This study examined changes in students’ photography learning outcomes following participation in a Coaching Clinic Instructional Model. A quantitative one-group pretest–posttest design was employed with 32 Grade XI students in the Visual Communication Design program at SMKN 6 Kota Jambi, Indonesia. The instructional model was implemented through three sequential phases: Conceptual Foundation, Guided Coaching, and Professional Workflow. Data were collected using a 20-item multiple-choice test covering technical photography concepts, visual composition, digital workflow, and professional ethics, supplemented by structured observation during the intervention. Students’ mean scores increased from 62.46 on the pretest to 78.57 on the posttest, representing an absolute improvement of 16.11 points. The aggregate-mean N-Gain was 0.43, indicating a moderate level of learning improvement. Positive changes were observed across the assessed photography learning domains, while classroom observations indicated that guided practice, immediate feedback, and professional workflow activities supported students’ engagement with the learning process. Nevertheless, device heterogeneity and limited instructional time constrained opportunities for extended practice. These findings provide initial evidence that a structured coaching-based approach can support photography learning in resource-constrained vocational education settings, although further studies using comparison groups and authentic performance assessments are required.